2014
DOI: 10.1007/s00256-014-2043-y
|View full text |Cite
|
Sign up to set email alerts
|

Cysts of the anterior horn lateral meniscus and the ACL: is there a relationship?

Abstract: Our results suggest that cysts adjacent to the AHLM may in part be explained by cysts or ganglia of the ACL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The transverse ligament and ACL can also be the origins. 65 Anterior lateral cysts extended medially either into the root or into the Hoffa fat pad, but in some cases, the type of extension did not correlate with the presence of an underlying meniscal tear. 54 Zheng et al 249 reported that preoperative anterior horn cysts showed worse patient-reported outcomes.…”
Section: Resultsmentioning
confidence: 96%
“…The transverse ligament and ACL can also be the origins. 65 Anterior lateral cysts extended medially either into the root or into the Hoffa fat pad, but in some cases, the type of extension did not correlate with the presence of an underlying meniscal tear. 54 Zheng et al 249 reported that preoperative anterior horn cysts showed worse patient-reported outcomes.…”
Section: Resultsmentioning
confidence: 96%
“…Macerated tear is closely associated with meniscus cyst which is mostly found between the AHLM and the anterior cruciate ligament [ 13 ]. Differing from the even network structure of meniscus body and posterior horn, the circumferential fibers of AHLM gather to be bundles, and the loose separation between circumferential fiber bundles generate micro gap.…”
Section: Discussionmentioning
confidence: 99%